The paleopathological collection of the “G. D’Annunzio” University Museum (Chieti-Pescara, Italy) - D'Anastasio, Ruggero; Di Fabrizio, Antonietta; Paolucci, Assunta; Del Cimmuto, Maria; Cilli, Jacopo; Capasso, Luigi (Medicina Historica, 2023)
Paleopathology is a multidisciplinary science which studies the origin and evolution of diseases. The main sources of information consist of biological remains (mainly bones and teeth), archaeological finds and historical documents. The study of diseases in prehistoric times is based solely on fossils showing pathological signs. The "G. d’Annunzio" University Museum of Chieti-Pescara (Italy) preserves a rich paleopathological collection consisting of 481 artifacts. The collection consists of plant, animal and human remains with pathological changes resulting from trauma, infectious diseases, joint diseases, tumors, metabolic diseases or nutritional deficiencies and congenital diseases. Each specimen has an inventory number and a technical data sheet, accompanied by photographic images from different viewpoints. The data sheet includes information regarding the taxonomic classification, the dating and origin of the specimen, the description of the lesion and offers a pathological diagnosis. It is a unique collection of its kind, which constitutes a precious source of information even on very ancient diseases, and an opportunity for researchers to study the interactions between ecosystems of the past and extinct animal and plant species through “paleopathological markers”.